Valuation of Livestock in Farms - Piotr Kica; Piotr Szczypa (Problemy Zarządzania, 2021)
Purpose: The aim of this article is to assess the possibility of applying the industry livestock valuation index as proposed by Karolina Pasula during the public defense of the doctoral dissertation “Directions and conditions for the standardization of accounting in agricultural enterprises” as an alternative method of valuation, taking into account sources of information and risk assessment on a farm. Methodology: The research process was divided into three main stages: (1) examining the possibility of applying the industry indicator for measuring biological assets proposed by K. Pasula for the valuation of livestock, i.e. pigs, as exemplified by a selected farm whose undertakings are known to the authors; (2) repeating the study from stage 1 on the valuation of dairy cattle as exemplified by the farm the activities of which are known to the authors; (3) on the basis of the conclusions of stage 1 and stage 2 studies, possible modification of the industry indicator for measuring biological assets, conducting research on a larger group of farms breeding livestock. Findings & value added: The conducted research confirmed the possibility of applying the analyzed ratio in the practice of entities that do not keep accounting books. The obtained results are characterized by high cognitive value as a measure of biological assets in relation to pigs. The valuation based on the industry measurement index in farms takes into account the risk which, as shown in the research, is an important factor influencing the value from the valuation.